Multiple PAR and E4BP4 bZIP transcription factors in Zebrafish: diverse spatial and temporal expression patterns - Ben-Moshe Livne, Zohar; Foulkes, Nicholas S. (Chronobiology international, 2010)
Circadian rhythms of physiology and behavior are generated by an autonomous circadian oscillator that is synchronized daily with the environment, mainly by light input. The PAR subfamily of transcriptional activators and the related E4BP4 repressor belonging to the basic leucine zipper (bZIP) family are clock-controlled genes that are suggested to mediate downstream circadian clock processes and to feedback onto the core oscillator. Here, the authors report the characterization of these genes in the zebrafish, an increasingly important model in the field of chronobiology. Five novel PAR and six novel e4bp4 zebrafish homolog genes were identified using bioinformatic tools and their coding sequences were cloned. Based on their evolutionary relationships, these genes were annotated as ztef2, zhlf1 and zhlf2, zdbp1 and zdbp2, and ze4bp4-1 to -6. The spatial and temporal mRNA expression pattern of each of these factors was characterized in zebrafish embryos in the context of a functional circadian clock and regulation by light. Nine of the factors exhibited augmented and rhythmic expression in the pineal gland, a central clock organ in zebrafish. Moreover, these genes were found to be regulated, to variable extents, by the circadian clock and/or by light. Differential expression patterns of multiple paralogs in zebrafish suggest multiple roles for these factors within the vertebrate circadian clock. This study, in the genetically accessible zebrafish model, lays the foundation for further research regarding the involvement and specific roles of PAR and E4BP4 transcription factors in the vertebrate circadian clock mechanism. (Author correspondence: yoavgtauex.tau.ac.il)
Gesehen am 19.07.2017